Enhanced UML Methodology with New Hybrid Diagrams: An ATM Application - Mohamed, Sherif Magdy (Journal of Education and Vocational Research, 2013)
Object oriented proved to be the most important software engineering tools. The main reason behind the importance is that, Object Oriented covers the most powerful programming languages such as Java and C++. UML is a modeling language which is a part of object oriented and it was created to provide the software development industry with analysis and design techniques based on some diagrams. The most common UML diagrams in use are Class and Activity diagram. To implement any system using object oriented UML, the programmer needs at least two or three diagrams beside the Use Case diagram in order to understand a full picture of the system. There is no diagram which can show the full picture of the system. In this research, new methodology called â€œTouch and Goâ€ has been generated by the researchers to implement the system. In this methodology, analysis and design are merged in one stage called Touch. Implementation and testing stage are merged in one stage called Go. The Class and Activity diagram are merged to introduce new integrated diagram called Enhanced Class Activity (ECA) diagram and the normal Activity diagram will be modified and improved as Activity Remarked Class (ARC) diagram. Analytical analysis of the new methodology is implemented in ATM machine system which can be later implemented using Java language or any other Object Oriented language. A powerful system like ATM is chosen to apply the new technique and it has been shown clearly how the methodology is working perfectly with such system. This study helps to reduce the number of diagrams that are being used to implement the system, reducing total time of implementation and making the coding stage easier by using only few numbers of diagrams.